Marriage of black phosphorus and Cu2+ as effective photothermal agents for PET-guided combination cancer therapy - Kuan Hu (Nature Portfolio, 2020)
A balance between high stability and rapid degradation is required for effective photothermal anti-cancer agents. Here, the authors use Cu2+ to accelerate the degradation of black phosphorus nanosheets while enhancing its photothermal ability and apply this material for PET-guided, CDT-enhanced combination cancer therapy in mice.